Development of speech test materials for Malay speaking paediatric population in Kuantan, Pahang : a preliminary study - Azhar, Aima Suhaily; Wan Ahmad, Wan Aslynn Salwani (2013)
The identification of suitability of some Malay words taken from Dewan Bahasa dictionary was investigated in this current study in preparation to develop a speech test materials for Malay speaking paediatric population in Kuantan, Pahang. 30 parents and 30 children were involves as the subjects in this study. The children were divided into three groups according to their age. There were 10 children in each age group : 3 years to 3 years and 11 months (3 – 3.11), 4 years to 4 years and 11 months (4 – 4.11), 5 years to 5 years and 11 months (5 – 5.11). The study was carried out in a quiet room at two nurseries and kindergarten around Kuantan, Pahang. The 110 words were selected from the dictionary and being represented by the picture in flash cards during the test. The familiarity of the words according to parents perception was evaluated as well as tested on children. Finally, 97 words were included in the final wordlist as the familiar words in targeted population and can be used to develop speech test.